Reducing the overuse of βhCG measurements in the emergency gynaecology clinic. Issue 1 (8th February 2016) - Frost, Lucy
Abstract: Serial βhCG testing can be a helpful tool in deciding how to manage pregnancy of unknown location. Its use in emergency gynaecology clinics can prevent unnecessary admission and intervention. However, despite NICE Guidelines on when it is safe to opt for conservative management, it was identified that there was a problem with over-testing of βhCG when patients could be discharged with instructions to repeat a urinary pregnancy test in two weeks. Two PDSA cycles were undertaken to improve the awareness of NICE guidelines: the first involved formal and informal educational sessions and the second involved the inclusion of a guideline summary on the front of patients' notes when they were having serial βhCG tests for doctors to refer to. Case notes were reviewed for 157 women who had βhCG tests at baseline and 48 hours. Of these, 139 were suitable for serial βhCG testing, and 83 of these were suitable for discharge after 48 hours. Of the 83 patients that were eligible for discharge, there were 31 unnecessary βhCG tests done, 23 of which were prior to intervention. A significant improvement was noted, with between 4-10 unnecessary βhCG tests per fortnight prior to intervention, 0-3 following the first intervention, and 0-2 following the second. Reduction in unnecessary βhCG testing has positive implications for patients, who do not have to take unnecessary time off work, prolong an already very distressing period, and have unnecessary blood tests. There are also cost and time saving implications for the hospital.